OPTIMIZATION OF LIGHTING DESIGN IN OFFICE SPACES WITHIN THE FRAMEWORK OF ENERGY CONSERVATION - Ainun Zakiyah; Lomi, Abraham; Handoko, Fourry (Journal of Sustainable Technology and Applied Science (JSTAS), 2025)
Lighting conditions in office building B of UNISMA have not met the SNI standard because each room has the same number of lights for different rooms; this results in a large amount of electricity consumption from the lighting sector. The installation of the number of lamp armatures should be in accordance with the area of ​​the room and then related to the function of the room and must also meet the standard lighting of the room (SNI 03 – 6575 – 2011.2011). For that, the calculation of the number of lamp armatures is appropriate for the standard and design of room lighting using Dialux software, where the office lighting standard is 350 Lux. Based on these steps, the lighting standard is produced approaching the SNI standard using Philips LED lights. With this design condition, the use of electrical energy becomes optimum and energy efficiency is achieved. Based on the Dialux software simulation, the percentage of savings in the initial conditions and design was 39%:61%.